TRAP1 functions in the morphogenesis of the embryonic kidney - Ha Eun Kim; Taejoon Kwon; Hyo Jung Sim; Tae Joo Park (Animal Cells and Systems)
TNF receptor-associated protein1 (TRAP1) is a mitochondrial molecular chaperon with high homology with a cytosolic chaperon HSP90. It has been shown that TRAP1 functions as an inhibitor for apoptosis by preventing cytochrome-c release from mitochondria. In addition, TRAP1 seems to play critical roles in metabolic processes for energy production, such as glycolysis and β-oxidation. It has also been reported that TRAP1 is a direct target of PTEN-induced kinase 1 (PINK1) and may be a cause of Parkinson’s disease (PD) in humans. Although the biochemical functions of TRAP1 are under intense study for the physiology and treatment of various cancers, its roles in vertebrate development have not been reported. This study shows that Xenopus TRAP1 is strongly expressed in the developing muscle, kidney, and brain tissues. Perturbation of TRAP1 function by treating TRAP1 inhibiter GTPP or microinjection of antisense-morpholino oligo (MO) caused mild defects in striated muscle fiber formation. Furthermore, the looping patterns of developing kidney tubules were perturbed, indicating that TRAP1 function is necessary for proper kidney development.